Mekong Regional Cooperation: Prospects for an Emergence of a New Regional Sectoral Mechanism - Le Lena, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
The Mekong region consists of six countries linked by the Mekong River, namely Cambodia, China, Laos, Myanmar, Thailand, and Vietnam. Since the early 1990s, regional cooperation in the Mekong region has gained new momentum and become more dynamic. Significant transformations in the trend of regionalism occurred with an increase in the number of multilateral mechanisms. Given the myriad of existing mechanisms, there is a question of whether there is any chance for a new sectoral cooperation mechanism. The following research seeks to answer that question by taking tourism cooperation as a case study. The research will explore current existing tourism cooperation frameworks and factors that influence regional tourism collaboration. It argues that there is room for a new tourism cooperation mechanism. However, there are also push and pull factors which must be taken into consideration as the potential institution is being built.Received 18th February 2020; Revised 12th September 2020; Accepted 20th September 2020